2016
DOI: 10.5296/ijssr.v4i1.8672
|View full text |Cite
|
Sign up to set email alerts
|

Traveller Perceptions of Trust in Air Traffic Controllers: A Cultural Comparison between India and the United States

Abstract: The aim of this research is to determine passengers' trust in air traffic controllers, based on the age and gender of the controller. The job of an air traffic controller is difficult in terms of the physical and mental stressors involved. The retirement age for controllers was instated in an effort to avoid issues relating to lack of capabilities. Decline in trust in an aging workforce has become a trend in certain areas. Similarly, gender inequality in the workplace and the sentiment that female employees ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
1
0
3
Order By: Relevance
“…Several consumer research studies have showed that emotions play a key role when a person is put in a situation that involves decision-making, and can be a mediating effect in relation to consumer opinions and trust (Mehta, Rice, & Rao, 2016;Mehta, Rice, Winter, & Buza, 2017;Rice, Winter, Kraemer, Mehta, & Oyman, 2015;Winter, Rice, Friendenreich, Mehta, & Kaiser, 2017;Winter, Rice, & Mehta, 2014). As mentioned in the previous section, emotions can cloud a person's ability to make sensible decisions.…”
Section: Affectmentioning
confidence: 99%
“…Several consumer research studies have showed that emotions play a key role when a person is put in a situation that involves decision-making, and can be a mediating effect in relation to consumer opinions and trust (Mehta, Rice, & Rao, 2016;Mehta, Rice, Winter, & Buza, 2017;Rice, Winter, Kraemer, Mehta, & Oyman, 2015;Winter, Rice, Friendenreich, Mehta, & Kaiser, 2017;Winter, Rice, & Mehta, 2014). As mentioned in the previous section, emotions can cloud a person's ability to make sensible decisions.…”
Section: Affectmentioning
confidence: 99%
“…A dimensão da similaridade pode ser entendida à medida que um cliente individual se sente semelhante com outros clientes, podendo identificar-se com estes no ambiente de serviço (Brocato et al, 2012;Mehta et al, 2016). A identidade social "permite que este indivíduo se localize nesse contexto" (Araujo et al, 2013, p. 4), ou seja, o cliente tende a se sentir mais confortável em ambientes que encontre pessoas semelhantes a ele (Cremer et al, 2015;Mehta et al, 2016).…”
Section: Referencial Teóricounclassified
“…A identidade social "permite que este indivíduo se localize nesse contexto" (Araujo et al, 2013, p. 4), ou seja, o cliente tende a se sentir mais confortável em ambientes que encontre pessoas semelhantes a ele (Cremer et al, 2015;Mehta et al, 2016). Quando o cliente se encontra em um ambiente frequentado por pessoas que apresentam essas características, avalia esse ambiente de maneira positiva dentro de um ambiente de varejo uma vez que, se sente mais compatível com os outros clientes (Brocato et al, 2012).…”
Section: Referencial Teóricounclassified
See 1 more Smart Citation